Depression and its associated factors among people living with HIV/AIDS in Kaski district, Nepal. - Khanal,Raghav (2019)
ABSTRACT: Background: Depression is a common mental disorder with indication such as sadness, loss of interest or pleasure, feelings of guilt or low self-worth, disturbed sleep or appetite, feelings of tiredness and poor concentration. PLHA are at a higher risk of mental disorder with a prevalence that is two to four times higher compared with comparable HIVnegative individuals or the general population. Objectives: The study had major objective to find the prevalence of depression and its associated factors among people living with HIV/AIDS in Kaski district Nepal. Methodology: The study design used was descriptive cross-sectional study design among People living with HIV/AIDS undergoing ART at Pokhara Academy of Health Science which is the only ART centre of whole Kaski district. All the registered cases under the ART were the study population (n=278).The depression assessment was done by Using Nepali Version Beck Depression Inventory and Semi structured questionnaire was used. Findings: The study found that the prevalence depression among PLWHAS in Kaski district, Nepal was (27.7%) with mild (13.3%) depression was highest, followed by moderate (8.6%) and severe (5.8%) depression. The Study found that different factor such sex, employment, educational status, discrimination, tobacco consumption etc were significantly associated with depression and the study also showed that female are more likely 2.577 more likely to have depression then men, illiterate were also 2.66 times more likely to have depression than literate respondents, etc. The study also showed that there is Negative Correlation between depression score and monthly income of respondent. Conclusion: The study concluded that the prevalence of depression among PLWHAS in Kaski district was (27.7%) and demographic, social, economic and behavioral factors like sex, educational status, income, discrimination, tobacco consumption, etc were significantly associated with depression.